MORPHOLOGICAL EVOLUTION, CLASSIFICATION AND PHYLOGENETIC OF DIFFERENCE SPECIES OF GENUS EUPHORBIA (EUPHORBIACEA)-A REVIEW - KHAN , SA; ZAHRA , A; MALIK , S; RAZA , A; SALEEM , F; ASLAM , U; ASGHAR , A; SAJJAD , M; AMEER , A; MARYAM , M; SAEED , I; SHAHEEN , A; et al. (Biological and Clinical Sciences Research Journal, 2024)
The present review paper focuses on the morphology, taxonomic categorization, and phylogenetic positioning of ten chosen species of Euphorbia, a large genus of the family Euphorbiaceae containing over 2000 species. The study starts with a general introduction to the genus, highlighting the importance of knowing the morphological variation and evolution in the group. A comparison of critical morphological features such as the type of leaf margining, structure of inflorescence, and presence of latex is made to understand the role of such traits in several species. The classification provides a detailed taxonomic breakdown of the ten species selected for review, pointing out the distinguishing character of each species. Evolutionary history within the genus is discussed phylogenetically using one or more molecular markers. The discussion brings together the conclusions from comparing the morphological characteristics of the studied species and the results of the analysis of their phylogenetic relationships concerning the problems of systematics and conservation. The research paper concludes by highlighting the significant findings and recommending further research on Euphorbia species employing diverse research methods.